Inquiry Learning Model to Improve Student's Quick Reading Ability - Siregar, Epi Supriyani; Kurniati, Rizki; Sagala, Ramlan Sahputera (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2021)
This research is based on problems related to the application of the inquiry learning model to improve students' speed reading skills, which so far have not been activated. The aim of the research is to find a valid, effective, and practical learning model to improve students' speed reading skills. The research method used is Gall, Gall and Borg development research. The research was conducted in a private elementary school in Medan. The learning model developed is equipped with learning tools, namely model books, lesson plans, teacher books, and student books. The product developed was carried out by individual trials, small group trials and field group trials. Furthermore, testing the effectiveness and practicality of the learning model. The research findings show: (1) the learning model developed is an inquiry learning model to improve the speed reading ability of elementary school students which consists of syntax, social system, reaction principle, support system, instructional impact and accompaniment. The learning model developed is equipped with tools, namely model books, lesson plans, teacher books, and student books. The whole set of inquiry learning models based on (2) the developed inquiry learning model is proven to be effective in improving student learning outcomes, this is proven by statistical testing t-test where the value of tcount (9.98) is higher than ttable (2 .00), and (3) the developed inquiry learning model has a practicality level with a score of 3.39 in the practical category without improvement.